Persuasive Strategies Used in Al Jazeera Arabic and Al Arabiya News Reports in the Death Incident of the Saudi Journalist Jamal Khashoggi: A Critical Discourse Analysis Perspective - الشبول، صبري شحادة; محفوظ، علاء (جامعة جرش, 2022)
تهدف الدراسة الحالية إلى الاستقصاء في استراتيجيات الأقناع المستخدمة في تقارير الجزيرة العربية والعربية الإخبارية في حادثة وفاة الصحفي السعودي جمال خاشقجي. كما تهدف إلى تحليل خطابات كلتا القناتين الإخباريتين بشكل نقدي وتقييم كيفية تمثيل "نحن" الإيجابية و"هم" السلبية. وتتكون بيانات الدراسة الحالية من تقريرين إخباريين مفصلين؛ أحدهما يعود لقناة الجزيرة العربية والآخر يعود لقناة العربية، اللذان يناقشان حادثة وفاة الصحفي السعودي. ويتم تحليل بيانات الدراسة الحالية في ضوء المربع الأيديولوجي لفان دايك. حيث أن البيانات جمعت في الفترة من الثاني إلى الثاني والعشرين من تشرين الأول/ أكتوبر 2018 من الموقعين الرسميين لكلتا القناتين الإخباريتين. وتكشف نتائج الدراسة الحالية أن "نحن" الإيجابية و"هم" السلبية في كلتا القناتين الإخباريتين يتم تمثيلهما من خلال الموارد والاستراتيجيات اللغوية مثل الأدلة، والمفردات، ونزع الشرعية، والتكرار، المبني للمعلوم والمبنى للمجهول، والافتراضات المسبقة. وعلاوة على ذلك، كشفت النتائج أيضا أن كلتا القناتين الإخباريتين قد استخدمتا استراتيجيات إقناع مختلفة، ألا وهي الأسئلة البلاغية، واللغة المجازية، والأدلة، وأسلوب القصة، ووجهة النظر، والصفات، واللغة الانفعالية، واستراتيجية الخوف، والتكرار، واختيار المفردات، والافتراضات المسبقة. The current study aims at investigating the persuasive strategies used in Al Jazeera Arabic and Al Arabiya news reports in the death incident of the Saudi journalist Jamal Khashoggi. It also aims to critically analyze the discourses of both news channels and evaluate how the positive “us” and negative “them” are represented. The data of the current study consist of two detailed news reports; one report belongs to Al Jazeera Arabic and the other belongs to Al Arabiya that discuss the death incident of the Saudi journalist. The data of the current study are analyzed in light of Van Dijk’s ideological square. The data are collected between the 2nd to the 22 of October 2018 from the official websites of both news channels. Findings of the current study reveal that the positive “us” and the negative “them” in both news channels are represented through linguistic resources and strategies such as evidentially, lexicons, DE legitimization, repetition, active and passive structures and presuppositions. Moreover, findings also revealed that both news channels have employed various persuasive strategies, namely rhetorical questions, figurative language, evidence, anecdote, point of view, adjectives, emotive language, fear strategy, repetition, lexical choice and presuppositions.
Keywords: القنوات الإخبارية -- الأساليب البلاغية -- خاشقجي، جمال أحمد حمزة، ت. 2018 م